Sensing and Magnetic Properties in Zn-CdFe2O4 Spinel Ferrite Doped with SnO2 Prepared by Sol-Gel Auto Combustion - Mariam O. Abd Alkareem; Tagreed M. Al-Saadi (Ibn Al-Haitham Journal for Pure and Applied Sciences)
The sol-gel method was used in this study to create the Zn-CdFe2O4/SnO2(0.15) nano ferrite, and XRD, FE-SEM, and EDX methods were used to evaluate the nano ferrite's characteristics. The findings showed that the lattice constant of the sample CdFe2O4/SnO2(0.15) is higher than that of ZnFe2O4/SnO2(0.15) and Zn0.5Cd0.5Fe2O4/SnO2(0.15) and that the resultant compound possesses a cubic spinel ferrite phase. The crystal size was on the nanoscale, according to Scherrer-Williamson Hall. Based on the FE-SEM images, it can be noticed its shape as semi-spherical or spherical; the presence of elements Zn, Cd, Fe, Sn, and O was confirmed by the EDX test. The gas sensing showed good sensitivity to NO2 gas and a short response and recovery time (15.3 sec, 49.5 sec). The magnetic properties were calculated using a vibrating sample magnetometer, where soft magnetic behavior was shown for all samples. The novel zinc cadmium ferrite preparation is expected to find use in a wide range of products, including biomedical equipment, motors, sensors for high-density data storage devices, and magnetic recording devices.